2008
DOI: 10.1090/conm/452/08777
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-period collapse and 𝐺𝐿_{𝑛}(ℤ)-scissors congruence in rational polytopes

Abstract: Quasi-period collapse occurs when the Ehrhart quasi-polynomial of a rational polytope has a quasi-period less than the denominator of that polytope. This phenomenon is poorly understood, and all known cases in which it occurs have been proven with ad hoc methods. In this note, we present a conjectural explanation for quasi-period collapse in rational polytopes. We show that this explanation applies to some previous cases appearing in the literature. We also exhibit examples of Ehrhart polynomials of rational p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 6 publications
1
38
0
Order By: Relevance
“…When P is a Fano polytope, we call r P the Gorenstein index. The minimum period common to the cyclic coefficients of L P * divides r P ; when the period does not equal r P we have a phenomena known as quasi-period collapse [7,16]. In general r P = r Q but, by Proposition 4, P * and Q * are Ehrhart equivalent.…”
Section: Example 8 Consider the Laurent Polynomialsmentioning
confidence: 99%
“…When P is a Fano polytope, we call r P the Gorenstein index. The minimum period common to the cyclic coefficients of L P * divides r P ; when the period does not equal r P we have a phenomena known as quasi-period collapse [7,16]. In general r P = r Q but, by Proposition 4, P * and Q * are Ehrhart equivalent.…”
Section: Example 8 Consider the Laurent Polynomialsmentioning
confidence: 99%
“…Furthermore, they showed that period collapse never occurs for G dim(P )−1 (P , ·). Haase and McAllister [10] gave a conjectural explanation of period collapse involving splitting the polytope into pieces and applying unimodular transformations onto these pieces.…”
Section: Introductionmentioning
confidence: 99%
“…The article [10] constructs examples for all dimensions ≥ 2 and for arbitrary denominator. For more information, the article [2] constructs simplices whose Ehrhart quasi-polynomial has coefficient functions with prescribed minimum periods, and the article [8] offers some conjectures for why the minimum period of L P (t) is sometimes strictly smaller than the denominator of P.…”
Section: Discussionmentioning
confidence: 99%